2013
DOI: 10.1021/om4006627
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Labilization of a Cyclometalating Ligand Applied to Auxiliary-Mediated Asymmetric Coordination Chemistry

Abstract: (4S)-4-Isopropyl-2-(3-nitrophenyl)-4,5-dihydrooxazole ((S)-Phox) is introduced as a novel chiral auxiliary for the asymmetric synthesis of ruthenium polypyridyl complexes. A simply accessible (S)-Phox-bearing precursor serves as the starting point for diastereoselective coordination chemistry: The stereogenic carbon atom of the cyclometalating auxiliary controls the spatial arrangement of incoming 1,10-phenanthrolines during ligand substitution reactions (ratio Λ:Δ up to 14:1), and further precipitation afford… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…These high energies cause blue devices to suffer from short operational lifetimes and poor device stability. , The degradation mechanisms of phosphorescent OLED devices are poorly understood and are highly variable between different device architectures . There are numerous reports of photoinduced decomposition processes and photosubstitution reactions in analogous ruthenium-based systems. Device degradation can be caused by chemical breakdown of any of various component layers in the emissive stack, including dopant molecules whose long lifetimes in the excited state increase the likelihood of damaging side reactions. ,− …”
mentioning
confidence: 99%
“…These high energies cause blue devices to suffer from short operational lifetimes and poor device stability. , The degradation mechanisms of phosphorescent OLED devices are poorly understood and are highly variable between different device architectures . There are numerous reports of photoinduced decomposition processes and photosubstitution reactions in analogous ruthenium-based systems. Device degradation can be caused by chemical breakdown of any of various component layers in the emissive stack, including dopant molecules whose long lifetimes in the excited state increase the likelihood of damaging side reactions. ,− …”
mentioning
confidence: 99%
“…Interestingly, at the same time Meggers et al reported a closely related behavior with a cyclometalated C ^N ligand different from ours (Scheme 3). On heating the compound obtained by coordinating a 1,10-phenanthroline (phen) to a tetrakis(acetonitrile) cycloruthenated derivative at 100 °C in chlorobenzene in the presence of 3,4,7,8tetramethyl-1,10-phenanthroline (tmephen), [67] they observed the coordination of a new bidentate ligand trans to C, which could only have been obtained with this stereochemistry if the phen had moved trans to N prior to the substitution of the MeCN moieties by the incoming tmephen ligand.…”
Section: Reactive Versus Non-reactive Complexesmentioning
confidence: 99%
“…Adapted from ref. [67] (4) the trans effect of the carbon atom), whereas the new isomer is formed under thermodynamic control, the isomerization being most likely due to a strong antisymbiotic effect of the carbon atom of the phenylpyridine. Interestingly, at the same time Meggers et al reported a closely related behavior with a cyclometalated C ^N ligand different from ours (Scheme 3).…”
Section: Reactive Versus Non-reactive Complexesmentioning
confidence: 99%
“…8 The use of chiral counterions has been long-known as a viable method to obtain cationic complexes in enantioenriched form by crystallisation. 3,9 While the use of chiral auxiliaries, which thermodynamically or kinetically control the configuration of an intermediate 10 or allow for the separation of diastereomers by column chromatography, 11 has over the last years become a practical method to isolate isomers with stereogenic Fe-, Ru-, Rh- and Ir-centres, this strategy not only requires the introduction of an auxiliary, but also the subsequent stereospecific substitution by an achiral ligand (Fig. 1C).…”
mentioning
confidence: 99%